A novel sesquiterpene and three new phenolic compounds from the rhizomes of Acorus tatarinowii Schott. Issue 19 (1st October 2015) - Liang, Shuang; Ying, Shu-Song; Wu, Hong-Hua; Liu, Yan-Ting; Dong, Peng-Zhi; Zhu, Yan; Xu, Yan-Tong
Graphical abstract